Differential impact of overt and subclinical hypothyroidism on severe postpartum hemorrhage: a retrospective cohort study - Zhuang, Jungou; Guo, Qiaoli; Liu, Chenning; Fu, Yujiao; Liu, Yuhui; Tang, Li; He, Fang (Frontiers in Endocrinology, 2025)
BackgroundThe impact of hypothyroidism, which can be divided into overt hypothyroidism and subclinical hypothyroidism, on severe postpartum hemorrhage (SPPH) remains unknown.MethodsA total of 34,303 pregnant women from the Third Affiliated Hospital of Guangzhou Medical University between 2016 and 2020 were included in this retrospective cohort study. We employed three logistic regression models incorporating different covariates to explore the relationship between hypothyroidism and SPPH, followed by an interaction analysis to identify potential modifiers. Then, we performed a stratified analysis to examine the influence of potential modifiers on the association between hypothyroidism and SPPH. Finally, sensitivity analyses were conducted to evaluate the robustness of our findings.ResultsIn the logistic regression analysis, we found that hypothyroidism was correlated with an elevated risk of SPPH (OR = 1.609, 95% CI: 1.111–2.329, p = 0.012). In addition, overt hypothyroidism had a significant impact on the increased risk of SPPH (OR = 1.688, 95% CI: 1.137–2.507, p = 0.009), whereas no significant association with SPPH was observed for subclinical hypothyroidism (OR = 1.208, 95% CI: 0.443–3.291, p = 0.712). In the relationship between hypothyroidism and SPPH, we observed that age and history of radiation exposure acted as potential modifiers (p for interaction < 0.05). Additionally, the correlation between hypothyroidism and SPPH was stronger in pregnant women aged < 35 years (OR = 2.412, 95% CI: 1.583–3.673, p < 0.001) than in those aged ≥ 35 years (OR = 0.755, 95% CI: 0.364–1.567, p = 0.450).ConclusionsOvert hypothyroidism had a significant impact on the elevated risk of SPPH, especially in pregnant women aged < 35 years. In contrast, subclinical hypothyroidism showed no significant association with SPPH, which may reflect limited statistical power rather than the absence of risk. These findings offer valuable insights into the relationship between hypothyroidism and SPPH, potentially optimizing maternal outcomes by preventing and intervening in the occurrence of SPPH.